TOI-2285b: A 1.7 Earth-radius planet near the habitable zone around a nearby M dwarf. (5th December 2021) - Fukui, Akihiko; Kimura, Tadahiro; Hirano, Teruyuki; Narita, Norio; Kodama, Takanori; Hori, Yasunori; Ikoma, Masahiro; Pallé, Enric; Murgas, Felipe; Parviainen, Hannu; Kawauchi, Kiyoe; Mori, Mayuko; et al.
Abstract: We report the discovery of TOI-2285b, a sub-Neptune-sized planet transiting a nearby (42 pc) M dwarf with a period of 27.3 d. We identified the transit signal from the Transiting Exoplanet Survey Satellite photometric data, which we confirmed with ground-based photometric observations using the multiband imagers MuSCAT2 and MuSCAT3. Combining these data with other follow-up observations including high-resolution spectroscopy with the Tillinghast Reflector Echelle Spectrograph, high-resolution imaging with the SPeckle Polarimeter, and radial velocity (RV) measurements with the InfraRed Doppler instrument, we find that the planet has a radius of 1.74 ± 0.08 R_, a mass of \!\!19.5 M_ (95% c.l.), and an insolation flux of 1.54 ± 0.14 times that of the Earth. Although the planet resides just outside the habitable zone for a rocky planet, if the planet harbors an H2 O layer under a hydrogen-rich atmosphere, then liquid water could exist on the surface of the H2 O layer depending on the planetary mass and water mass fraction. The bright host star in the near-infrared ( K s = 9.0) makes this planet an excellent target for further RV and atmospheric observations to improve our understanding of the composition, formation, and habitability of sub-Neptune-sized planets.